Outcomes of Total Knee Arthroplasty in Patients with Prior Hardware: A Case–Control Study Using Handheld Navigation - Malhotra, Rajesh; Jain, Aditya; Gupta, Saurabh; Gautam, Deepak (The Journal of Knee Surgery, 2021)
Presence of hardware in juxta-articular location poses challenge during total knee arthroplasty (TKA). When present in distal femur, it precludes the use of an intramedullary femoral jig during TKA often necessitating removal of hardware leading to prolonged surgery, higher risk of complications, and inferior results. We conducted a case–control study to assess the outcome of TKA among patients with post-traumatic arthritis using a handheld navigation system to perform bone cuts allowing retention of hardware in situ. In 15 patients with post-traumatic arthritis and hardware around the knee (Group A), none or part(s) of hardware were removed while performing TKA. These patients were matched to 15 patients who underwent TKA with handheld navigation for primary OA knee (Group B). The perioperative outcomes assessed were operative time, intraoperative blood loss, length of hospital stay, complications, and 30 days reoperation rate. Clinical outcomes were assessed by using Knee Society Score (KSS) and radiological outcomes using mechanical axis and coronal and sagittal component angles. Mean age of patients at surgery were 65.67 years (Group A) and 66.73 years (Group B). Mean operative time and blood loss were significantly higher in Group A as compared with Group B. At the mean follow-up of 34 months, KSS significantly improved in both the groups. However, there was no statistically significant difference in the clinical and radiological outcomes between the two groups. One patient in Group A developed wound dehiscence and had to undergo debridement and flap coverage within 30 days. The use of navigation helps surgeons in gaining proper limb alignment and implant positioning without complete removal of hardware.
Keywords: post-traumatic arthritis; prior hardware; total knee arthroplasty; handheld navigation